2011
DOI: 10.1002/mrd.21410
|View full text |Cite
|
Sign up to set email alerts
|

The methylation patterns of the IGF2 and IGF2R genes in bovine spermatozoa are not affected by flow‐cytometric sex sorting

Abstract: The objectives of this study were to investigate the effect of sexing by flow cytometry on the methylation patterns of the IGF2 and IGF2R genes. Frozen-thawed, unsorted, and sex-sorted sperm samples from four Nellore bulls were used. Each ejaculate was separated into three fractions: non-sexed (NS), sexed for X-sperm (SX), and sexed for Y-sperm (SY). Sperm were isolated from the extender, cryoprotectant, and other cell types by centrifugation on a 40:70% Percoll gradient, and sperm pellets were used for genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 41 publications
(64 reference statements)
0
17
0
8
Order By: Relevance
“…IVF results are also affected by sperm concentration, which needs to be higher than for IVF with unsorted sperm, and by the hydrodynamic pressure used for sorting (BarceloFimbres et al 2011). Although the sorting process has significant effects on sperm viability, and bull effects are obvious, compromised DNA does not affect reduced fertility as most non-viable spermatozoa, and those with aneuploidies are out-gated from sorting by parallel Similarly, bisulphide sequencing of Nellore bull spermatozoa DNA indicated that the sorting process by flow cytometry does not affect the overall DNA methylation patterns of the insulin-like growth factor 2 (IGF2) and IGF2 receptor (IGF2R) genes in sperm, although individual variation in methylation patterns among bulls was observed (Carvalho et al 2012).…”
Section: Ivf With Sorted Spermatozoamentioning
confidence: 99%
“…IVF results are also affected by sperm concentration, which needs to be higher than for IVF with unsorted sperm, and by the hydrodynamic pressure used for sorting (BarceloFimbres et al 2011). Although the sorting process has significant effects on sperm viability, and bull effects are obvious, compromised DNA does not affect reduced fertility as most non-viable spermatozoa, and those with aneuploidies are out-gated from sorting by parallel Similarly, bisulphide sequencing of Nellore bull spermatozoa DNA indicated that the sorting process by flow cytometry does not affect the overall DNA methylation patterns of the insulin-like growth factor 2 (IGF2) and IGF2 receptor (IGF2R) genes in sperm, although individual variation in methylation patterns among bulls was observed (Carvalho et al 2012).…”
Section: Ivf With Sorted Spermatozoamentioning
confidence: 99%
“…Durante o processo de sexagem, os espermatozoides podem sofrer danos na sua estrutura, comprometendo sua viabilidade (BLONDIN et al, 2009;CARVALHO et al, 2010). Desta forma, várias características espermáticas, tais como motilidade, integridade de membrana, integridade de acrossoma, integridade de cromatina, capacidade de gerar blastocisto e perfil de mRNA, tem sido avaliadas (BOE-HANSEN et al, 2005;MORTON et al, 2007;BLONDIN et al, 2009;CARVALHO et al, 2010).…”
Section: Discussionunclassified
“…Desta forma, várias características espermáticas, tais como motilidade, integridade de membrana, integridade de acrossoma, integridade de cromatina, capacidade de gerar blastocisto e perfil de mRNA, tem sido avaliadas (BOE-HANSEN et al, 2005;MORTON et al, 2007;BLONDIN et al, 2009;CARVALHO et al, 2010). Entretanto, nenhum destes estudos avaliou se o processo de sexagem poderia causar alguma mudança epigenética no YOUNG et al, 2001;KANG et al, 2001;LONG;CAI, 2007 London, v. 460, p. 473-478, 2009b. HEALY, A.A.; HOUSE, J.K.; THOMSON, P.C.…”
Section: Discussionunclassified
See 2 more Smart Citations